STUDENTS’ DEVELOPMENT OF LEXICAL SKILLS THROUGHOUT ENGLISH SESSIONS (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2024)
Acquiring proficiency in a foreign language has long since transcended its status as a trendy pastime and is now considered a vital necessity. A young specialist needs to be able to speak at least one foreign language in order to advance in their job. Our main goal is to teach the student to fully and competently express his point of view on a given problem because the Federal State Educational Standard requires that after mastering the foreign language discipline, the student must be able to communicate (orally and in writing) in a foreign language on topics related to daily life and the workplace.